Bardeen–Petterson alignment, jets, and magnetic truncation in GRMHD simulations of tilted thin accretion discs. Issue 1 (26th April 2019) - Liska, M; Tchekhovskoy, A; Ingram, A; van der Klis, M
ABSTRACT: Prevalent around luminous accreting black holes, thin discs are challenging to resolve in numerical simulations. When the disc and black hole angular momentum vectors are misaligned, the challenge becomes extreme, requiring adaptive meshes to follow the disc proper as it moves through the computational grid. With our new high-performance general relativistic magnetohydrodynamic (GRMHD) code H-AMR, we have simulated the thinnest accretion disc to date, of aspect ratio H / R ≈ 0.03 ≈ 1.7°, around a rapidly spinning ( a ≈ 0.9) black hole, using a cooling function. Initially tilted at 10°, the disc warps inside ∼5 rg into alignment with the black hole, where rg is the gravitational radius. This is the first demonstration of Bardeen–Petterson alignment in MHD with viscosity self-consistently generated by magnetized turbulence. The disc develops a low-density high-viscosity (αeff ∼ 1.0) magnetic-pressure–dominated inner region at r ≲ 25 rg that rapidly empties itself into the black hole. This inner region may, in reality, due to thermal decoupling of ions and electrons, evaporate into a radiatively inefficient accretion flow if, as we propose, the cooling time exceeds the accretion time set by the order unity effective viscosity. We furthermore find the unexpected result that even our very thin disc can sustain large-scale vertical magnetic flux on the black hole, which launches powerful relativistic jets that carry 20\!-\!50 per cent of the accretion power along the angular momentum vector of the outer tilted disc, providing a potential explanation for the origin of jets in radio-loud quasars.